Exploring Greenland: Science and Technology in Cold War Settings - Heymann, Matthias; Knudsen, Henrik; Lolck, Maiken; Nielsen, Henry; Nielsen, Kristian; Ries, Christopher (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 2010)
This paper explores a vacant spot in the Cold War history of science: the development of research activities in the physical environmental sciences and in nuclear science and technology in Greenland. In the post-war period, scientific exploration of the polar areas became a strategically important element in American and Soviet defence policy. Particularly geophysical fields like meteorology, geology, seismology, oceanography, and others profited greatly from military interest. While Denmark maintained formal sovereignty over Greenland, research activities were strongly dominated by U.S. military interests. This paper sets out to summarize the limited current state of knowledge about activities in the environmental physical sciences in Greenland and their entanglement with military, geopolitical, and colonial interests of both the USA and Denmark. We describe geophysical research in the Cold War in Greenland as a multidimensional colonial endeavour. In a period of decolonization after World War II, Greenland, being a Danish colony, became additionally colonized by the American military. Concurrently, in a period of emerging scientific internationalism, the U.S. military “colonized” geophysical research in the Arctic, which increasingly became subject to military directions, culture, and rules.